2019
DOI: 10.1177/1082013218823129
|View full text |Cite
|
Sign up to set email alerts
|

Potential of lactic acid bacteria from Pico cheese for starter culture development

Abstract: Autochthonous lactic acid bacteria may provide a means of promoting the quality and safety of traditional fermented food products, in particular, artisanal cheeses. Pico cheese is an artisanal, dairy specialty of the Azores in risk of disappearing. Efforts to maintain its quality to the requirements of the modern markets are, thus, necessary. Lactic acid bacteria were isolated from artisanal Pico cheese, identified by sequencing of the 16S rRNA gene, and their potential as starter cultures was evaluated by stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 34 publications
4
28
2
1
Order By: Relevance
“…Leuconostocs are part of the core microbiota in several artisanal cheeses, albeit their populations are, in general, numerically lower than those of lactococci [83]. The main species described in starter free cheeses from Portugal were Ln.…”
Section: Dairy Productsmentioning
confidence: 98%
See 1 more Smart Citation
“…Leuconostocs are part of the core microbiota in several artisanal cheeses, albeit their populations are, in general, numerically lower than those of lactococci [83]. The main species described in starter free cheeses from Portugal were Ln.…”
Section: Dairy Productsmentioning
confidence: 98%
“…In most cheeses, lactobacilli are part of the native microbiota, with several species represented. Ten lactobacilli species have been reported in Portuguese artisanal cheeses, manufactured without the addition of a commercial starter: L. casei [83,84], L. paracasei [83][84][85][86][87], Latilactobacillus curvatus [84], L. plantarum [84][85][86][87], L. acidophilus, Lactobacillus delbrueckii [84], Lentilactobacilus otakiensis [83,85,86], Levilactobacillus brevis, Limosilactobacillus fermentum [84]. Lactobacilli, for example, L. paracasei, Lacticaseibacillus rhamnosus, L. plantarum, and L. curvatus play a role in cheese ripening [73].…”
Section: Dairy Productsmentioning
confidence: 99%
“…Isolation of enterococcal strains with good acidification properties from artisanal cheeses is not frequent, and comprised only 3.6 to 11.6% of the enterococcal isolates in Pico and Pecorino Abruzzese cheeses, respectively [174,175]. In several studies, the enterococci have been reported to exhibit a poor acidifying capacity, with only a small percentage of the isolates being able to produce acid enough for pH to drop below 5.0-5.2 upon incubation for 16-24 h at 37 • C [176][177][178].…”
Section: The Technological Roles and Potentialities Of Enterococci Inmentioning
confidence: 99%
“…Casein degradation plays a role not only upon cheese flavor and texture, but also upon the accumulation of bioactive peptides, with potential health benefits, within the product matrix [7]. Caseinolytic strains have been isolated from artisanal cheeses to variable proportions (17-95%) of the total enterococcal isolates [153,174,175,180]. The gelE gene, frequently regarded as a virulence factor, is involved in caseinolysis when the enterococci grow in dairy substrates.…”
Section: The Technological Roles and Potentialities Of Enterococci Inmentioning
confidence: 99%
See 1 more Smart Citation